A comparative study of some the morphological characteristics of the leaves and fruits of three date palm cultivars Phoenix dactylifera L. in Hadhramout Valley- Yemen. - Bahurmuz, Yasser Saeed (Basrah Journal Of Date Palm Research, 2023)
This study was conducted on three cultivars of date palm (Jazza, Magraf and Maktoumi) planted in valley Hadhramout, Yemen, in the agricultural season 2023 AD to examine the differences in the morphological characteristics of the leaves and fruits of the aforementioned varieties. and the results were analyzed using the complete sectoral design. The results obtained showed that the cultivar factor has a clear effect on the number of leaves, the length of the Spine, the number, length and width of the pinnaes, and in all the studied traits in relation to the morphological characteristics of the fruits. In terms of leaves, the cultivar Jazzaz was significantly superior in the number of pinnaes, reaching 213.4 pinnaes. And the Magraf cultivar was Significantly superior in the number of leaves, reaching 105.7 leaves, while Maktoumi cultivar was significantly superior in Spine length, pinnaes length and width, reaching 15.68 cm, 55 cm, and 3.88 cm. As for the fruits, the variety Magraf was significantly superior in the length of the fruit. It reached 41.05 mm, while Maktoumi cultivar was significantly superior in width, weight and volume of the fruit. It reached 25.67 mm, 16.67 g, and 17.50 cm3.